Financial Literacy and Quantitative Reasoning in the High School and College Classroom - Annamaria Lusardi; Dorothy Wallace (Numeracy, 2013)
This overview frames the eight articles devoted to financial literacy in this issue of Numeracy. The survey questions used to assess financial literacy in the United States, Romania, France, Switzerland, Australia, and elsewhere include mathematics that is routinely covered in mathematics and quantitative reasoning courses. Financial literacy, wherever it is received, appears to benefit people throughout their lives. The close tie between quantitative and financial literacy may be exploited to introduce more of both into the high school and undergraduate curriculum.